Holmium laser enucleation of the prostate in patients with preexisting inflatable penile prostheses. Issue 4 (9th June 2022) - Virani, Shohaib; Kleinguetl, Colin; Bird, Erin T.; Tayeb, Marawan M. El
Abstract: This retrospective study evaluated the safety and efficacy of holmium laser enucleation of the prostate (HoLEP) in patients with an inflatable penile prosthesis (IPP). Five men with a preexisting IPP underwent HoLEP for obstructive lower urinary tract symptoms at Baylor Scott and White Medical Center between January 2016 and September 2020. None of the patients had preexisting prostate malignancy or urethral strictures. Minimal blood loss was seen during HoLEP, with an average length of hospital stay of 1.4 days and an average time of catheterization of 1.4 days. None of the patients had any known postoperative complications, including need for transfusions, return to the operating room for postoperative bleeding, or clot evacuation. In conclusion, there was no increased risk of perioperative or postoperative complications for HoLEP in this group compared with the general population. HoLEP appears to be a safe and efficacious method for the treatment of lower urinary tract symptoms in patients with a preexisting IPP.